An Exploratory Study on Management Competence for Better Work Practices of The Traditional Metal Fabrication Industry in Kumasi, Ghana - Peggy Ama Fening; Isaac Kwabena Agyei; Dickson Adom (Indonesian Academy of Social and Religious Research (IASRR), 2023)
One of the identifiable resources that an industry can utilize as a driver for survival is managerial competence. Although literature is replete with evidence on this subject matter, no research work has been conducted on the relationship between managerial competence and performance of the traditional metal fabrication industries in Ghana. To address this information gap, this study explored the work place practices of three traditional metal craft industries in Kumasi, Ghana with managerial competence as a moderating factor. An inductive research approach based on qualitative research methodology was adopted. The target population was 300 people of which a sample size of 171 respondents was selected. Data were collected through the use of questionnaire designed with open and close-ended responses as well as personal observations conducted using a well-designed observation guide with clear attributes and angles of observation. The results showed that all the study participants interviewed exhibited various levels of operational competence of knowledge, technical skills, experience and character attitude needed to enhance the performance and day-to-day administration of their work. They also had good conflict resolution abilities and good decision-making skills, as well as an excellent apprenticeship system embodied in a succession plan. On the other hand, the study identified several factors that impacted negatively on the operations of their work including the inability to create a conducive work environment for high performance, poor equipment and tool maintenance culture, lack of proper PPEs, poor record keeping, poor innovation and creativity skills, and nonexistence of a system for the acquisition and utilization of modern equipment and technology. These limitations suggest lack of management competence. The study considers this as quite worrisome and recommends for the needed support from both governmental and NGOs, to safeguard the survival of the metal craft industry in Ghana.